1985
DOI: 10.5271/sjweh.2215
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among employees of lead battery plants and lead-producing plants, 1947-1980.

Abstract: Mortality among employees of lead battery plants and lead-producing plants, . Scand J Work En viron Health II (1985) 331-345. Two cohorts of male lead workers, 4 519 battery plant workers and 2 300 lead production workers, all of whom had been employed for at least one year during the period I January 1946 through 31 December 1970, were observed for mortality during the 34 years from 1 Januar y 1947 through 31 December 1980. Vital status as of the closing date was determined for 94.7 lifo of the former grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
3
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 35 publications
2
55
3
3
Order By: Relevance
“…In a death certificate study of battery and lead production workers in the United States, a significant excess risk of death from hypertension was found, but the authors observed that this finding was partially explained by changes in the ICD coding of hypertensive renal disease (17). Although mortality rates from hypertension were not available in our study for calculating expected events, we observed a reduction in mortality from cardiovascular diseases and, particularly, from ischemic heart disease.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…In a death certificate study of battery and lead production workers in the United States, a significant excess risk of death from hypertension was found, but the authors observed that this finding was partially explained by changes in the ICD coding of hypertensive renal disease (17). Although mortality rates from hypertension were not available in our study for calculating expected events, we observed a reduction in mortality from cardiovascular diseases and, particularly, from ischemic heart disease.…”
Section: Discussioncontrasting
confidence: 49%
“…Negative results have been reported for battery workers (15) and glass workers (1 6), two occupational groups which usually experience lower exposures to the metal than smelter workers. Results from 6 lead production facilities and 10 battery plants in the United States found excess risks of stomach cancer and lung cancer, both inversely related to the length of employment, and no excess risk of kidney cancer (17). However, only 2 deaths from kidney cancer occurred, and they were among workers in lead smelting, refining, and recycling who had 11-20 years of employment and who started work before 1946 (SMR 800).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This accumulation has been shown to compromise some ability of bone cells to respond to hormones and also may result in alterations in the plasma levels of 1,25-dihydroxy-vitamin D 3 (Goyer, 1993;Pounds et al, 1991). Long-term exposure to Pb 2+ may also result in a nephropathy or renal adenocarcinoma (Baker et al, 1980;Buchet et al, 1980;Cooper et al, 1985;Fowler, 1993;Lilis, 1981;Goyer, 1982Goyer, , 1993Selevan et al, 1985).…”
Section: Leadmentioning
confidence: 99%
“…One problem with studies of primary smelter workers is the concomitant exposure to other metals (24)(25)(26); this problem also exists for lead-exposed workers (27). Increased lung cancer mortality and morbidity has been connected with exposure to arsenic, which has been reported in several epidemiologic studies (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%